The effect of 'health education' on perception of health with face-to-face verbal and brochure techniques in Northern Cyprus - Necipoglu, Dilay; Bebis, Hatice (Routledge Journals, Taylor & Francis Ltd, 2022)
This study has been conducted with the design of a quasi-experimental research method. This study aimed to determine what effect 'health promotion and education' has on the perception of the health, which has been conducted face-to-face and with brochure during house visits. In this quasi-experimental study between 20 July and 20 September 2020 of the Dikmen Region in North Cyprus. The sample size of the study was evaluated with G*Power and a total of n = 80 people (face-to-face verbal group = 40; brochure group = 40) were included in the study. The data were collected using the 'Socio-Demographic Question Form' and Perception of Health Scale'. A post-test was applied 2 weeks after the education. SPSS 21.0 software was used for the statistical analysis of the data obtained. The necessary permissions were obtained in order to carry out the study. The mean age for face-to-face verbal group was 55.28 (SD = 16.53), and for brochure technique group was 46.28 (SD = 16.01). At the beginning of the study, it was found that the groups were similar in terms of socio-demographic variables and the mean health perception scale score, and there was no statistically significant difference between them (p > 0.05). After the Perception of Health education, a statistically significant difference was seen between the pre-test and post-test health perception score mean in both groups (p < 0.05); however, a statistically significant difference was not found between the different methods (p > 0.05). In this study, it was determined that face-to-face verbal and brochure techniques were effective in increasing the health perception of the health education given.
Keywords: Perception of health; face to face; brochure; health education